Prevalence And Risk Factor Analysis Of Gastrointestinal Parasites In Relation To Environmental Conditions In Different Agro-Climatic Zones Of Rajasthan (India) (Applied Biological Research, 2017)
An epidemiological survey in relation to environmental conditions covering all  most the entire agro-climatic zones of Rajasthan (India) was conducted to  determine the prevalence of gastrointestinal parasitism in crossbred and local  cattle. A total of 733 faecal samples (464 cattle and 269 buffaloes) were  collected and screened from dairy animals by sedimentation and floatation  technique. The overall prevalence of was 22.5%, with Semi-arid Eastern plain  zone at higher infection risk (48.25%); followed by Arid Western zone  (30.43%). Lowest infection was recorded from Transitional plain of Luni  Basin zone (4.11%). Regarding different species of parasite, highest infection  was recorded of Balatidium coli (10.10%) followed by Strongyle eggs (5.46%)  and lowest was of Toxocara vitulorum and Moniezia expansa (0.82%). In  relation to various risk factors Indigenous animal displayed higher risk of  infection as compare to cross-bred cattle (OR = 4.36, 95% CI = 29.60 - 63.84).  Older animals have higher risk of infection as compared to young one (OR =2.03, 95% CI = 13.59 - 30.44). Female are more prone to significant infection  as compared to their male counterpart (OR = 1.94, 95% CI = 11.38 - 33.42).  Samples screened during monsoon season depicted highest level of infection  (OR = 45.99, 95% CI = 39.00 - 53.14). Farms having other companion animal  have more incidence of infection (23.45%) as compared to other farms (OR = 1.22, 95% CI = 8.07 - 18.66).
Keywords: Gastro-intestinal parasites; faecal examination; agro-climatic zone; Rajasthan